075 Sexual Function and Problematic Use of Smartphones and Online Social Networking Sites. (1st May 2022) - Costa, R.; Martins, C; Fuzeiro, V; Gonçalves, C; Deus, P; Santos, Rolo A
ABSTRACT: Introduction: Use of new technologies, such as smartphones and online social networks, becomes problematic when it acquires addictive-like qualities that interfere in well-being and important activities. Problematic use of smartphones and online social networks has been related to many forms of psychopathology. Investigation supports that sexual function may be disturbed by addictive-like use of online social networking, but research on the topic is surprisingly scarce. Objectives: To examine correlations between sexual functioning and problematic use of smartphones and online social networking sites. Method: The sample was obtained by aggregating data from four studies that collected information on sexual function and problematic use of smartphones and/or online social networks by means of online surveys. The total number of participants was 1, 446 respondents (mostly Portuguese). There were 1, 166 participants providing information on smartphone use, and 683 providing information on use of online social networking sites. Measures included the Female Sexual Function Index (FSFI), the International Index of Erectile Function (IIEF-15), the Smartphone Addiction Scale (Short Version), and the Internet Addiction Test (IAT) specifically adapted to use of online social networking sites. Results: In women, more problematic use of online social networking sites correlated with lower desire (rho = -.11, p = .011), lower arousal (rho = -.20, p < .001), lesser lubrication (rho = -.15, p = .001), difficulties having orgasms (rho = -.25, p < .001), sexual dissatisfaction (rho = -.25, p < 001), coital pain (rho = -.21, p < .001), and sexual distress (rho = .38, p < .001). In men, more problematic use of online social networking sites correlated with lower erectile function (rho = -.29, p < .001), difficulties having orgasms (rho = -.23, p = .003), dissatisfaction with intercourse (rho = -.18, p = .024), and general sexual dissatisfaction (rho = -.36, p < .001), but not with desire (rho = -.14, p = .075). Correlations of sexual function with problematic use of smartphones followed similar trends, but in a weaker and less consistent manner. In women, problematic use of smartphones correlated with lower arousal (rho = -.11, p = .001), difficulties lubricating (rho = -.17, p < .001), difficulties having orgasms (rho = -.19, p < .001), dissatisfaction (rho = -.10, p = .002), pain (rho = -.22, p < .001), and sexual distress (rho = -.24, p < .001), but not with desire (rho = -.06, p = .077). In men, problematic use of smartphones correlated with lower erectile function (rho = -.20, p = .002), but not with the other dimensions of sexual functioning (-.11 < rho < -.07, p > .10). In regressions models, sexual difficulties were not predicted by problematic smartphone use after controlling for problematic use of online social networks, which was the only significant predictor. Entering age as additional predictor did not influence the results. Conclusions: Problematic use of online social networks appears to be associated with sexual difficulties. Problematic smartphone use might not be associated with sexual difficulties independently of addictive-like engagement in online social networking. Disclosure: Work supported by industry: no.